Competency-Based Career Development Strategy in the Industrial Era 4.0 - Suparjo Suparjo; Charisha Mahda Kumala; Yoga Adhi Dana (BUSMI : Journal of Business and Management Innovations, 2025)
Over The purpose of this study was to determine the influence of technical competence, non-technical competence, training and development, and organizational policies on the career development of lecturers. The population that also served as a sample was 228 lecturers at the University of 17 August 1945 Semarang. SEM analysis tool. The results of the study showed that technical competence, non-technical competence, training and development, and organizational policies had a significant influence on the career development of lecturers. The results of the study of technical competence, non-technical competence, training and development, and organizational policies have a positive and significant effect on career development. The results of this statistical analysis offer an in-depth understanding of the complex dynamics underlying career development in the Industry 4.0 era, emphasizing the importance of a multidimensional approach that integrates competency development, appropriate training interventions, and supportive organizational policies in facilitating sustainable and adaptive careers amidst digital transformation.